Wybrane aktywizujące metody nauczania w pracy z uczniem na przykładzie lekcji podstaw przedsiębiorczości - Elżbieta Małgorzata Nyga (Przedsiębiorczość - Edukacja, 2006)
The subject of entrepreneurship needs an affective attitude of a teacher who: - besides he or she has got great knowledge about the subject he/she is at the same time careful about good and achievements of his or her students, - he or she has got knowledge about the teaching - learning process, - he or she knows different methods and ways of working. This kind of the teacher is a reflective and experienced person. He knows not only „what?” should be taught but also „how?” and „why?”.This teacher accepts behaviours that are described by Schoen, and he aims at the professional perfection. He thinks teaching of Entrepreneurship is a permanent process which is connected with him and his students. During every stage of learning process, teacher plays the roles: an organizer of a teaching process, a tutor, a carer, and an adviser who helps students to find new ways of a personal development. /diagram 1/ The teacher has to assume the teaching aims which come up to requirements of educational and examination standards. It is explained in a the diagram 2. The article does not deal with teaching in a comprehensive way. It is only a focus on methods and techniques of work with a student while using a script „Etyka i korupcja w biznesie” (Ethics and Corruption in Business). The methods and techniques are based on NLP- neuro-linguistic programming of student’s work. It is based on teaching by experience that is D. Kolb’s cycle. You will understand better both issues if you look at diagram 3 and 4. The most important for understanding the essence of the teaching by experience is acquainting readers with teacher, s and learner, s duties (diagram 5 and 6). On the next pages of the article there are some practical hints about using active student methods: brainstorming, map of thoughts, importance hierarchy triangle, fish skeleton, panel discussion. If you illustrate and schematically show the teacher above methods it will be easier for him to select them with a syllabus and lesson organization. At the end of the article there is an outline of a two-hour lesson. During the lesson, students will be able to acquire skills of distinction some different basic ideas and ethical and unethical behaviours in business. Learners will know laws and institutions that protect a society from corruption and corrupting. The outline shows not only the order of the lesson, but describes in details the teacher, s and students,  behaviours. For every operation we weed specified time. It suggests the sources of information that can be useful while we are executing the syllabus during the lesson. There are presumable learner, s achievements after the lesson. There is a game Bingo titled „Are You Contaminated by Corruption?” in the enclosure.